Recent Research in English Urban History, c. 1450-1650 - Tittler, Robert (Urban History Review / Revue d'histoire urbaine, 1982)
Interest in few areas of English history has developed as fast in the last decade as in the pre-industrial urban setting. Where there were few serious academics at work and little instruction at the undergraduate level, we now have an entire — and very impressive — Open University course on the field, and the genre of urban case studies seems to have replaced the shire as favoured ground for English doctoral theses in history. Much of the recent work on pre-industrial urban problems continues to probe questions raised a decade or more ago. These studies, which deal with political factionalism, constitutional development, town-crown relations and similar problems, must not be dismissed as obsolete; the enormous diversity of the subject itself necessitates a great number of case studies before generalizations may be obtained. Equally important and perhaps more innovative in method are those studies of fresher conceptualization, typically more interdisciplinary in approach and more inclined towards quantitative methodology. These rely heavily on the work of the anthropologist, the demographer and geographer and have in a short time greatly expanded the bounds of the historian of the pre-industrial town and city.